Children and Adults Prefer the Egocentric Representation to the Allocentric Representation - Hu, Qingfen; Yang, Ying; Huang, Zhenzhen; Shao, Yi (Frontiers in Psychology, 2018)
We studied the strategy preference of using the egocentric or the allocentric representation in individuals who have acquired the abilities to use both representations. Fifty-seven children aged 5-7 years and 53 adults retrieved toys hidden in one of four identical containers in a square room. We varied the type of spatial representation available in four conditions: (1) only self-motion information (egocentric representation); (2) only external landmark cues (allocentric representation); (3) both self-motion and landmark cues (dual representation); (4) self-motion and landmark cues in conflict (conflict trial). We found that, compared with the allocentric representation, the egocentric representation approached maturity earlier in development and was exploited better in early years. More importantly, in the conflict trials, while both children and adults relied more on egocentric representation, still a small portion of participants chose allocentric representation, especially in the adult group. These results provided evidence that egocentric representation is generally preferred more in both young child and adults.